THE LEVELS OF IL-6, CRP, and LDH IN THE VITREOUS HUMOUR OF DIABETIC RETINOPATHY PATIENTS. - Singh, Kalyan; Khan, Perwez; Khan, Lubna; Mohan, Shalini; Singh, Parul; Agarawal, Surbhi; Patel, Namrata; Datta, Ditsha (International Journal of Retina, 2024)
Introduction: Diabetic retinopathy (DR) is a significant complication of diabetes mellitus (DM) and remains a leading cause of vision loss among working-age individuals. Level of inflammatory biomarkers rise in DR. Main focus on Interleukin-6(IL-6), C-Reactive Protein (CRP) and Lactate Dehydrogenase (LDH) as IL-6 induces excess production of VEGF, CRP has both pro-inflammatory and anti-inflammatory properties whereas, LDH acts through oxidation process on pyruvate to be converted into lactate. Altered lactate levels reflect changes in glucose metabolism rates or pyruvate levels. Methods: Prospective hospital-based cross-sectional study was carried out on diagnosed cases of Diabetic Retinopathy at a tertiary care centre. Selection of 50 patients was done as per inclusion criteria and exclusion criteria. Results: Among NPDR patients, Mean of IL-6 levels was 23.59 ± 19.02, LDH was 99.46 ± 51.17 CRP was 0.49 ± 0.30 whereas in PDR patients, Mean of IL-6 was 58.91 ± 26.50, LDH was 202.5 ± 63.93 and CRP was 0.93 ± 0.33 showing 2-fold raised in PDR patients. Conclusion: Our study emphasizes the crucial role of inflammatory biomarkers in the pathogenesis of diabetic retinopathy. The elevated levels of IL-6, LDH, and CRP in vitreous humor samples from PDR patients compared to NPDR patients indicate the activation of an inflammatory pathway during the disease’s progression. This research paves the way for further investigations into targeted therapies that can modulate these inflammatory mediators, potentially improving the prognosis of diabetic retinopathy.